Fine-mapping and functional studies highlight potential causal variants for rheumatoid arthritis and type 1 diabetes - Westra, Harm-Jan; Martínez-Bonet, Marta; Onengut-Gumuscu, Suna; Lee, Annette; Luo, Yang; Teslovich, Nikola; Worthington, Jane; Martin, Javier; Huizinga, Tom; Klareskog, Lars; Rantapaa-Dahlqvist, Solbritt; Chen, Wei-Min; et al. (Nature genetics, 2018)
To define potentially causal variants for autoimmune disease, we fine-mapped 1 , 2 76 rheumatoid arthritis (11,475 cases, 15,870 controls) 3 and type 1 diabetes loci (9,334 cases, 11,111 controls) 4 . After sequencing 799 1-kilobase regulatory (H3K4me3) regions within these loci in 568 individuals, we observed accurate imputation for 89% of common variants. We defined credible sets of ≤5 causal variants at 5 rheumatoid arthritis and 10 type 1 diabetes loci. We identified potentially causal missense variants at DNASE1L3, PTPN22, SH2B3, and TYK2, and noncoding variants at MEG3, CD28–CTLA4, and IL2RA. We also identified potential candidate causal variants at SIRPG and TNFAIP3. Using functional assays, we confirmed allele-specific protein binding and differential enhancer activity for three variants: the CD28–CTLA4 rs117701653 SNP, MEG3 rs34552516 indel, and TNFAIP3 rs35926684 indel. Fine-mapping and functional studies highlight potential causal risk variants for rheumatoid arthritis and type 1 diabetes, including missense variants at DNASE1L3, PTPN22, SH2B3, and TYK2, and noncoding variants at MEG3, CD28–CTLA4, and IL2RA.